MAXIMUM SECURITY PRISON DESIGN(Pendekatan pada Humanis Desain dan Eko Arsitektur) - Al Habib, Rizqi Azhar, Nur Rahmawati S, ST. MT, Ir. Alpha Febela P, MT (2015)
The reason of designing the maximum security prison is caused by the unsatisfied supporting facilities and the room capacity, as well as the system which is applied in a prison that has dismisses the humanism characteristic. Maximum Security Prison is a kind of prison based on the level of security. It is the highest level of security prison used for prisoners who possess the arrest time (15-20 years), lifetime imprisonment, or dead penalty with the criminal case such as murdering, terrorism, genocide, or the other humanism criminals. The design employs Humanism Design and Eco-Architecture approaches. Humanism design concerns on a human as a main of observing, a basic component of planning, or the last evaluation design. Whereas Eco-Architecture is the architecture planning that considers the environment interaction. It means the profitable interaction as it is applied on the building which can use the environment potential and preserve its environment condition. The result of this design is the kind of prison that contains two design characteristics. It is also completed with the maximum security level as a place for educating prisoners that can fulfill their main necessity by applying the building design which can interact with the environment.